Development of TPACK-Based Digital Learning Curriculum for Elementary School Teachers - Silalahi, Rizal Efendi; Koto, Fahri Nugraha; Putri, Diana Kirani (International Journal of Educational Insights and Innovations, 2025)
Digital transformation in education requires teachers to have competencies that are not limited to pedagogy and content, but also technology. This study aims to develop a digital learning curriculum based on the TPACK (Technological Pedagogical Content Knowledge) framework that can be implemented by elementary school teachers to improve the quality of the learning process in the digital age. A research and development (R&D) approach was used, adapting the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). During the analysis phase, teachers' needs for technology integration in learning were identified through observation and interviews. The analysis results were used to design a curriculum that balances and contextualizes technological, pedagogical, and content aspects according to the needs of elementary school teachers. The developed curriculum prototype was then validated by curriculum experts, educational technology experts, and experienced teachers. The validation results indicated that the curriculum has a high level of feasibility in terms of content relevance, TPACK component integration, and its effectiveness in teaching practice. Subsequently, the curriculum was implemented on a limited basis in several elementary schools and evaluated through questionnaires and observation of implementation. The evaluation results showed an increase in teachers' competencies in effectively integrating technology into the teaching and learning process.